Relationship between Hypnosis for Pain Management in Labor and Adverse Neonatal Outcomes: A Systematic Review - Majid Khadem-Rezaiyan; Reza Saeidi; Masumeh Ghazanfarpour; Mohamadghasem Etemadi Mashhadi; mona najaf najafi (Mashhad University of Medical Sciences, 2018)
Background: Many techniques have been proposed to relieve labor pain, one of which is hypnotherapy, which can be defined as the usage of hypnosis during labor to alleviate pain or anxiety. The aim of this systematic review was to examine the possible relationship between hypnosis and neonatal outcomes based on the available reports. Methods: Major databases, including PubMed, Web of Science, Scopus, and Cochrane CENTRAL, were systematically searched up to February 6, 2018. In the next stage, the titles and abstracts of the retrieved articles were reviewed to identify the relevant studies. The quality of the studies was evaluated using the Jadad scale. Study appraisal and data extraction were carried out by one of the authors, and then double-checked by another researcher. Finally, the search process resulted in the inclusion of 10 trials. Results: Based on eight studies, hypnosis for pain management during labor had no effect on Apgar score in neonates. No significant difference was reported between hypnosis and non-hypnosis groups in terms of the number of admission to the Neonatal Intensive Care Unit (NICU). Furthermore, the short-term effect of hypnosis on the continuation of exclusive breastfeeding was indicated in three studies. However, the duration of neonatal admission to nursery or NICU was not reported in any of the studies. Only one study reported that there was no significant difference between hypnosis and control groups concerning the frequency of hospital readmission. Conclusion: Based on the evidence reported in the literature, it could be concluded that hypnosis can be regarded as a safe approach for pain management during the labor. Moreover, this intervention did not show to exert any adverse effects on neonatal health status.